LEVERAGING MIGRATION FOR AFRICAN DEVELOPMENT: CHALLENGES AND PROSPECTS - Victor H Mlambo; Xolani Thusi; Luyanda Mtshali; Mandisa Makhathini; Nompumelelo Dlamini (Universitas PGRI Madiun, 2022)
This paper examines whether Africa can leverage migration for its economic development. Migration and the resulting remittances lead to increased incomes and poverty reduction, improved health and educational outcomes, and promote economic development. The paper employed a qualitative research approach where a review of the literature was undertaken. The functionalist theory was employed to examine migratory patterns and their association with development. The paper revealed that Africa has ample opportunities to leverage migration for development. However, for this to happen, there is a need to consolidate remittance channels, improve migration management frameworks and support the integration of migrants, Additionally, governments in Africa need to change the way they perceive migration, rather than observing migration as a threat, there is need to observe migration as a process which has the potential to contribute to the development of the continent